The programmable valve of a ventriculoperitoneal shunt for hydrocephalus - Valença, Marcelo Moraes; Silva, Ana Cristina Veiga da; Bem Junior, Luiz Severo; Ribeiro, Elayne Cristina de Oliveira; Valença, Marcelo Andrade; Silva, Alberto Henrique Torres Trindade da; Carvalho, Déborah Emmily de; Valença, Martina Falcão (Avanços em Medicina, 2025)
The programmable valve of a ventriculoperitoneal shunt for hydrocephalus